Sustainable Development and the Literacy of Women and Girls. Issue 3 (May 2017) - Callister, Lynn Clark
Abstract : Many women and girls in developing countries are illiterate. Literacy and health are closely related. As literacy improves, so does the health of women and girls, while maternal morbidity and mortality decreases. Our global health nursing expert, Dr. Callister, discusses the relationship between literacy and maternal child health worldwide and what organizations are doing to help.